Students’ Difficulties in Speaking English as a Foreign Language: Undergraduate Students’ Voices - Dwi Bayu Saputra; Eko Saputra; Lia Haryana; Adelia Puspa (Universitas Tidar, 2023)
Even though there has been a wide range of research on students' English-speaking issues, there has been little research on concerns associated with perceived difficulties in speaking, particularly in post-pandemic. This study aims to investigate the difficulties experienced by EFL students in speaking. The method used is exploratory sequential mixed methods in which qualitative data support quantitative data. Two data collection techniques were deployed to triangulate the data. Questionnaires were distributed to 105 students to discover their perceptions of difficulties in speaking after the pandemic. Then, eight students were interviewed to dig deeper into the data from the completed questionnaire. This study revealed that students in English study programs still had problems communicating owing to psychological and linguistic reasons. Some of the explanations identified by this research include a lack of English vocabulary, a lack of confidence while speaking English, and nervousness about receiving negative criticism from colleagues or lecturers. The study’s findings are intended to add to the body of knowledge concerning students’ speaking issues. It is hoped that teaching practitioners will be able to identify the right approach to teaching speaking so that learning may be done more efficiently.